Cost-sharing models: experience of the Anatolian University Libraries Consortium - Cuhadar, Sami; Cimen, Ertugrul (Elsevier Science Inc, 2019)
Purpose: This study examines the cost-sharing models used by the Anatolian University Libraries Consortium (ANKOS) to determine the amounts that university libraries pay for each consortial subscription. A survey was conducted among library directors and managers of ANKOS member universities to evaluate cost-sharing models in order to create improved models. The data obtained from the questionnaire were analyzed in SPSS, the first time that these cost-sharing models have been assessed on the national level. The results of the study are presented for the benefit of other consortia and scientists/researchers and library professionals working in the field. Design/methodology/approach: This article takes a historical and descriptive approach and uses statistical methods to analyze the results of the survey. It also focuses on obtaining objective results from the Consortium members' feedback. Findings: As with other library consortia all over the world, many different cost-sharing models have been used by ANKOS. As a result of this study, the most suitable models have been determined for different scales of academic libraries. In negotiations with publishers and vendors, priority will be given to price models preferred by member institutions. Practical implications: The material presented should be useful for all academic librarians concerned with consortium systems, cost-sharing, and e-resource management, especially in the developing world. This paper also provides some key points for academic librarians in the process of establishing a consortium. Originality/value: This paper is an example of successful academic library consortium activities in a developing country and examines, in detail, the developments, opportunities, and challenges experienced since the establishment of the consortium.
Keywords: Cost-Sharing Models; University Libraries; Anatolian University Libraries Consortium (Ankos); Turkey; Open Access